ASPEK SOSIAL EKONOMI PENGUSAHAAN SAGU DI MALUKU - R Supriadi; lsmatul Hakim (Jurnal Penelitian Hasil Hutan, 1991)
In the province of Maluku,  sago was and is still considered  an essential staple food for  the local people.  Sago flour is consumed   either for  sustenance  needs  or as a commercial  commodity.   For industrial  needs,  sago  is processed   to become  raw material for food,  textile,  wood adhesive,  fodder, cosmetics,  pharmaceuticals,  pesticides,  chemicals  and others.  This paper  described  several socio-economic   indicators  in sago related activities as a research result  in Maluku.fl  is concluded   that,  in general,  the education  level  of  respondents   are primary  school.   Most  of  them  have  already  a long  time  ago experience  in harvesting  of sago  trees at least for  7 years.   They  inherit their land ownershif  from  their ancestors,  and  the average family  land use patterns  consist  of  54.32 m2 for  house  building/construction,    966.36  m2 for  home  garden,  and  2.88   hectares for sago  garden.The income  distribution  among  several  activities of  the farmers  (respondents)   is as followed   :